High-strength concrete containing steel fibers and its use in protective equipment
Patent Information
- Application Number
- CN202611259608.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-30
AI Technical Summary
然而,钢纤维混凝土流动性较差,影响混凝土的强度,无法满足防护设备的使用需求
本发明通过静电自组装将磺酸基改性罗望子胶牢固负载于短切钢纤维表面,制得改性短切钢纤维,在混凝土中可充分发挥钢纤维自身刚性增强相与罗望子胶柔性界面层的协同增效作用。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete technology, specifically to a high-strength concrete containing steel fibers and its application in protective equipment. Background Technology
[0002] Protective equipment is a crucial barrier ensuring the safety of national defense and civil air defense projects. Currently, protective doors at project entrances and exits typically employ reinforced concrete or steel structures. However, protective doors made of ordinary concrete generally suffer from excessive weight and thickness, and are difficult to scale up. Steel fiber reinforced concrete is a novel multiphase composite material formed by incorporating randomly distributed short steel fibers into ordinary concrete. Because the randomly distributed steel fibers effectively inhibit the propagation of micro-cracks and the formation of macro-cracks within the concrete, it significantly improves the tensile, flexural, impact, and fatigue resistance of concrete, transforming it from a brittle material into a composite material with certain plastic properties. Research shows that the incorporation of steel fibers can effectively enhance the energy dissipation and impact resistance of concrete, effectively inhibiting crack initiation and propagation under impact loads, and enhancing structural stability.
[0003] Therefore, steel fiber reinforced concrete (SFR) has been increasingly widely used in protective engineering due to its excellent crack-resistant, toughening, and impact-resistant properties. In this field, SFR is mainly used in applications requiring high material performance, such as blast protection and penetration resistance, including bunkers, air-raid shelters, protective doors, and military transportation engineering. Existing research shows that using high-strength steel fiber reinforced concrete to reinforce and construct new blast-resistant projects can effectively improve the safety performance of structures when subjected to explosive impacts. The bridging effect of steel fibers can suppress the generation and propagation of cracks and the splashing and collapse of fragments under high-speed impact during penetration, transforming the failure mode of concrete under high-speed impact from pulverization to a state where it still retains relatively good integrity. However, SFR has poor fluidity, affecting the strength of the concrete and failing to meet the requirements of protective equipment.
[0004] In conclusion, there is an urgent need to develop a new type of steel fiber reinforced concrete material that combines high strength and good durability to meet the increasingly stringent performance requirements of protective equipment. Summary of the Invention
[0005] In order to solve the problems mentioned in the background art, the present invention aims to provide a high-strength concrete containing steel fibers and its application in protective equipment.
[0006] The objective of this invention can be achieved through the following technical solutions: A high-strength concrete containing steel fibers comprises the following raw materials measured in parts by weight: Silicate cement: 320-400 parts; Coarse aggregate: 650-820 parts; Fine aggregate: 480-600 parts; Modified chopped steel fiber: 15-25 parts; Fly ash: 200-260 parts; Water-reducing agent: 80-120 parts; Water: 150-250 parts; The modified chopped steel fibers are obtained by loading biomass gum onto the surface of chopped steel fibers; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate and modified chopped steel fiber into a high-speed mixer and mechanically mix at 300-500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
[0007] As a further embodiment of the present invention, the coarse aggregate is crushed stone with a particle size of 10-20 mm; the fine aggregate is sand with a particle size of 5-10 mm.
[0008] As a further aspect of the present invention, the method for preparing the modified chopped steel fiber includes the following steps: Step 1: Disperse the chopped steel fibers in toluene, then add an organic modifier and a catalyst to the mixture. After the addition is complete, turn on the heater and raise the temperature to 90-100℃. Continue to stir and maintain the temperature for 8-12 hours. Stop the heating, cool down and discharge the material. Filter out the fiber product, and after washing and drying, obtain the organic chopped steel fibers. Step 2: Disperse the organic chopped steel fibers in water, then add sulfonic acid-modified tamarind gum. After addition, stir and mix well, turn on the ultrasonicator, and ultrasonically treat at an ultrasonic frequency of 80-100kHz for 1-2 hours. Then continue stirring at a stirring rate of 200-400r / min for 6-9 hours. Filter out the material, and after washing and drying, obtain the modified chopped steel fibers.
[0009] As a further aspect of the present invention, in step one, the organic modifier is 5-carboxypentyltriphenylphosphine bromide.
[0010] As a further aspect of the present invention, in step one, the catalyst is aminosulfonic acid or p-toluenesulfonic acid.
[0011] As a further aspect of the present invention, in step two, the sulfonic acid-modified tamarind gum is prepared by the following method: Tamarind gum was added to pyridine and stirred until homogeneous. Then, sulfonic acid group-modifying reagent was added. After the addition was complete, the mixture was mechanically mixed and heated to 90-100℃. The mixture was kept at this temperature for 1-3 hours. After the reaction was completed, ethanol was added to precipitate the precipitate. The precipitate was filtered, washed, and dried to obtain sulfonic acid group-modified tamarind gum.
[0012] As a further embodiment of the present invention, the sulfonic acid group modifying agent is chlorosulfonic acid.
[0013] It should be noted that in the above technical solution, firstly, under the action of a catalyst, the surface of chopped steel fibers is modified with an organic modifier, so that the surface of the steel fibers carries quaternary phosphine cations, thus obtaining organic chopped steel fibers. In aqueous solution, the sulfonic acid groups in the sulfonic acid-modified tamarind gum structure will ionize to generate sulfonic acid anions, which can electrostatically adsorb the quaternary phosphine cations of the organic chopped steel fibers through electrostatic interaction, thereby completing the electrostatic assembly modification on the surface of the chopped steel fibers. Thus, biomass tamarind gum is loaded on the surface of the chopped steel fibers, and modified chopped steel fibers are obtained.
[0014] The sulfonic acid-modified tamarind gum was prepared by sulfonating tamarind gum in a pyridine solution using a sulfonic acid-modifying agent.
[0015] As a further aspect of the present invention, the fly ash is Class II fly ash.
[0016] As a further aspect of the present invention, the water-reducing agent is any one of naphthalene-based water-reducing agents or polycarboxylate water-reducing agents.
[0017] An application of high-strength concrete containing steel fibers, wherein the high-strength concrete is used in protective equipment.
[0018] The beneficial effects of this invention are: This invention uses electrostatic self-assembly to firmly load sulfonic acid-modified tamarind gum onto the surface of chopped steel fibers, thus producing modified chopped steel fibers. In concrete, these modified chopped steel fibers can fully leverage the synergistic effect of the rigid reinforcing phase of the steel fibers and the flexible interface layer of the tamarind gum.
[0019] First, steel fibers, as a three-dimensional randomly distributed reinforcement with high elastic modulus and high tensile strength, can effectively bridge microcracks inside concrete. During loading, they dissipate a large amount of fracture energy through mechanisms such as fiber pull-out, yielding, and fracture, thereby significantly improving the compressive strength and crack resistance of concrete. In this invention, sulfonic acid-modified tamarind gum is firmly loaded onto the surface of steel fibers through electrostatic self-assembly. This organic interface layer is not a simple coating, but rather forms a deep synergy with the steel fibers, complementing each other functionally.
[0020] During the dispersion stage, the loaded tamarind gum ionizes to generate sulfonic acid anions, imparting a strong negative charge and steric repulsion to the fiber surface, effectively breaking up fiber aggregates. Combined with its hydrophilic lubrication and water-retaining thickening properties, it allows individual steel fibers to be uniformly suspended and dispersed in the slurry, ensuring a "numerous and uniform" reinforcing foundation for the steel fibers from the source. During the interfacial bonding stage, the active groups (sulfonic acid groups, hydroxyl groups) in the tamarind gum molecules chemically bond with cement hydration products (such as CSH gel and calcium ions), optimizing the originally loose fiber-matrix interface transition zone into a dense, high-bonding load-bearing layer, significantly enhancing the interfacial bond strength. When the concrete cracks under load, the optimization of the originally loose fiber-matrix interface transition zone into a dense, high-bonding load-bearing layer greatly improves the bonding and anchoring efficiency of the steel fibers. Thus, under load, the steel fibers can be fully activated to efficiently transfer stress through pull-out or yielding, avoiding failure due to premature debonding.
[0021] During the crack-resistant energy dissipation stage, rigid steel fibers bear the principal tensile stress and inhibit the penetration of macroscopic cracks, while viscoelastic tamarind molecular chain segments slip and deform at the tip of microcracks, acting as a buffer layer to absorb additional impact energy, forming a dual impact resistance mechanism of "rigid load-bearing + flexible energy dissipation". Its synergistic effect far exceeds the simple sum of using steel fibers alone or adding polymers alone.
[0022] In summary, this invention achieves synergistic gains between steel fibers and the matrix by directional functionalization modification of steel fibers with tamarind gum, thereby deeply coupling the rigidity enhancement effect of steel fibers with the dispersion regulation, chemical bonding, viscoelastic energy dissipation, and protective functions of the interface modification layer. This results in a significant improvement in the overall mechanical and workability of concrete by enhancing the steel fibers' ability to disperse, improve interfacial adhesion, crack resistance, and durability.
[0023] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] In the following examples and comparative examples, the silicate cement grade is 52.5; the coarse aggregate is crushed stone with a particle size of 10-20mm; the fine aggregate is sand with a particle size of 5-10mm; the fly ash is Class II fly ash; and the water-reducing agent is LonS-50 high-efficiency water-reducing agent.
[0026] Example 1 This embodiment provides a high-strength concrete containing steel fibers, comprising the following raw materials measured in parts by weight: Silicate cement: 320 parts; Coarse aggregate: 650 parts; Fine aggregate: 480 parts; Modified chopped steel fiber: 15 parts; Fly ash: 200 parts; Water-reducing agent: 80 parts; Water: 150 portions; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate and modified chopped steel fiber into a high-speed mixer and mechanically mix at 500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
[0027] The method for preparing the modified chopped steel fiber includes the following steps: Step 1: Disperse 2.4g of chopped steel fibers in toluene. Then add 0.9g of 5-carboxypentyltriphenylphosphine bromide and 0.1g of p-toluenesulfonic acid to the resulting mixture. After the addition is complete, turn on the heater and raise the temperature to 95℃. Continue to heat and stir for 9 hours. Then stop the heating, cool down and discharge the material. Filter out the fiber product, wash and dry it to obtain organic chopped steel fibers. Step 2: Add 1.6g of tamarind gum to 20mL of pyridine, stir and mix well, then add 0.5g of chlorosulfonic acid. After the addition is complete, mix mechanically, turn on the heater and raise the temperature to 95℃. Keep the temperature at this temperature for 2h. After the reaction is complete, add ethanol to precipitate. The precipitate is filtered, washed and dried to obtain sulfonic acid modified tamarind gum. Step 3: Disperse 1.5g of organic chopped steel fibers in water, then add 4.8g of sulfonic acid-modified tamarind gum. After addition, stir and mix well, turn on the ultrasonicator, and ultrasonically treat at a frequency of 100kHz for 1 hour. Then continue stirring at a stirring rate of 300r / min for 8 hours. Filter out the material, wash and dry it to obtain modified chopped steel fibers.
[0028] Example 2 This embodiment provides a high-strength concrete containing steel fibers, comprising the following raw materials measured in parts by weight: Silicate cement: 350 parts; Coarse aggregate: 750 parts; Fine aggregate: 520 parts; Modified chopped steel fiber: 24 parts; Fly ash: 240 parts; Water-reducing agent: 110 parts; Water: 200 portions; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate and modified chopped steel fiber into a high-speed mixer and mechanically mix at 500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
[0029] The preparation method of the modified chopped steel fiber is the same as that in Example 1.
[0030] Example 3 This embodiment provides a high-strength concrete containing steel fibers, comprising the following raw materials measured in parts by weight: Silicate cement: 400 parts; Coarse aggregate: 820 parts; Fine aggregate: 600 parts; Modified chopped steel fiber: 25 parts; Fly ash: 260 parts; Water-reducing agent: 120 parts; Water: 250 portions; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate and modified chopped steel fiber into a high-speed mixer and mechanically mix at 500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
[0031] The preparation method of the modified chopped steel fiber is the same as that in Example 1.
[0032] Comparative Example 1 This comparative example provides a concrete comprising the following raw materials measured in parts by weight: Silicate cement: 350 parts; Coarse aggregate: 750 parts; Fine aggregate: 520 parts; Organic chopped steel fiber: 24 parts; Fly ash: 240 parts; Water-reducing agent: 110 parts; Water: 200 portions; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate, and organic chopped steel fibers into a high-speed mixer and mechanically mix them at 300-500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
[0033] The preparation method of the organic chopped steel fiber is the same as that in Example 1.
[0034] Comparative Example 2 This comparative example provides a concrete comprising the following raw materials measured in parts by weight: Silicate cement: 350 parts; Coarse aggregate: 750 parts; Fine aggregate: 520 parts; Short-cut steel fibers: 24 parts; Fly ash: 240 parts; Water-reducing agent: 110 parts; Water: 200 portions; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate and chopped steel fiber into a high-speed mixer and mechanically mix at 300-500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
[0035] Test case The concrete from the examples and comparative examples was poured into molds to make test blanks that met the specifications, and cured for 7 days. Mechanical strength tests were conducted according to standard GB / T 50081-2019; Crack resistance performance was tested according to standard JC / T 951-2005; The test results are recorded in the table below: Table 1 - Test Results
[0036] Test results show that concrete blanks made with modified chopped steel fibers have excellent mechanical strength and crack resistance, which can meet the requirements of protective equipment.
[0037] After replacing the modified chopped steel fibers with organic chopped steel fibers, the chopped steel fibers can be relatively evenly dispersed in the concrete due to electrostatic effects, thus still exhibiting good reinforcing effects. However, the interaction between tamarind gum and cement hydration is lost, resulting in the steel fiber's reinforcing effect not being fully realized.
[0038] Replacing modified chopped steel fibers with unmodified chopped steel fibers makes it difficult to disperse them fully, resulting in poor performance of various properties of the concrete blanks.
[0039] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.
[0040] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength concrete containing steel fibers, characterized in that, Including the following raw materials measured in parts by weight: Silicate cement: 320-400 parts; Coarse aggregate: 650-820 parts; Fine aggregate: 480-600 parts; Modified chopped steel fiber: 15-25 parts; Fly ash: 200-260 parts; Water-reducing agent: 80-120 parts; Water: 150-250 parts; The modified chopped steel fibers are obtained by loading biomass gum onto the surface of chopped steel fibers; The method for preparing the concrete includes the following steps: Step 1: Pour coarse aggregate, fine aggregate and modified chopped steel fiber into a high-speed mixer and mechanically mix at 300-500 r / min to form a precursor material; The second step is to add silicate cement, fly ash, and water-reducing agent to the precursor material, continue to stir evenly, then add water and stir until well mixed.
2. The high-strength concrete containing steel fibers according to claim 1, characterized in that, The coarse aggregate is crushed stone with a particle size of 10-20 mm; the fine aggregate is sand with a particle size of 5-10 mm.
3. The high-strength concrete containing steel fibers according to claim 1, characterized in that, The method for preparing the modified chopped steel fiber includes the following steps: Step 1: Using an organic modifier, under the action of a catalyst, the surface of chopped steel fibers is modified to obtain organic chopped steel fibers. Step 2: Disperse the organic chopped steel fibers in water and perform electrostatic assembly modification using sulfonic acid-modified tamarind gum to obtain modified chopped steel fibers.
4. The high-strength concrete containing steel fibers according to claim 3, characterized in that, In step one, the organic modifier is 5-carboxypentyltriphenylphosphine bromide.
5. The high-strength concrete containing steel fibers according to claim 3, characterized in that, In step one, the catalyst is aminosulfonic acid or p-toluenesulfonic acid.
6. The high-strength concrete containing steel fibers according to claim 3, characterized in that, In step two, the sulfonic acid-modified tamarind gum is prepared using the following method: Tamarind gum was added to pyridine and stirred until homogeneous. Then, sulfonic acid group-modifying reagent was added. After the addition was complete, the mixture was mechanically mixed and heated to 90-100℃. The mixture was kept at this temperature for 1-3 hours. After the reaction was completed, ethanol was added to precipitate the precipitate. The precipitate was filtered, washed, and dried to obtain sulfonic acid group-modified tamarind gum.
7. The high-strength concrete containing steel fibers according to claim 6, characterized in that, The sulfonic acid group modifying agent is chlorosulfonic acid.
8. The high-strength concrete containing steel fibers according to claim 1, characterized in that, The fly ash is Class II fly ash.
9. The high-strength concrete containing steel fibers according to claim 1, characterized in that, The water-reducing agent is either a naphthalene-based water-reducing agent or a polycarboxylate water-reducing agent.
10. An application of high-strength concrete containing steel fibers as described in claim 1, characterized in that, The high-strength concrete is used in protective equipment.